2017
DOI: 10.1007/s00268-017-4411-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between the Prognostic Nutritional Index and Morbidity/Mortality During Intestinal Resection in Patients with Ulcerative Colitis

Abstract: Lower O-PNI may predict the prognosis in patients with UC. O-PNI may be a useful indicator for decision-making regarding surgical timing and procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…CRP is a sensitive indicator reflecting whether the body is infected or not. CRP has been reported to increase significantly when infection occurs after resection (22). A study has also shown that TNF-α is the initial factor of inflammatory response in SAP complicated with PP.…”
Section: Discussionmentioning
confidence: 96%
“…CRP is a sensitive indicator reflecting whether the body is infected or not. CRP has been reported to increase significantly when infection occurs after resection (22). A study has also shown that TNF-α is the initial factor of inflammatory response in SAP complicated with PP.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the negative correlation between hs-CRP and CFR was found in IBD patients in remission. The association of lower PNI levels with mortality/morbidity in UC patients undergoing surgery has been shown in another novel study 27 . In our study, lower PNI levels were found to be associated with decreased CFR in IBD patients in remission.…”
Section: Discussionmentioning
confidence: 78%
“…There were no statistically significant differences for mortality in ICU between the low OPNI group (18.6%) and the high OPNI group (13.3%) (P=0.027). The median (IQR) length of stay in ICU was 17 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) days and 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) days for the low OPNI group and the high OPNI group, respectively (P=0.042).…”
Section: Resultsmentioning
confidence: 99%